The Oncogene LRF Stimulates Proliferation of Mesenchymal Stem Cells and Inhibits Their Chondrogenic Differentiation. (October 2013) - Yik, Jasper H.N.; Li, Huan; Acharya, Chitrangada; Kumari, Ratna; Fierro, Fernando; Haudenschild, Dominik R.; Nolta, Jan; Di Cesare, Paul E.
Objective: The oncogene leukemia/lymphoma-related factor (LRF) enhances chondrosarcoma proliferation and malignancy. This study aimed to investigate the roles of LRF in chondrogenic differentiation of primary human bone marrow–derived mesenchymal stem cells (BMSCs). Design: LRF was overexpressed in BMSC by lentiviral transduction. Chondrogenic differentiation of BMSC was induced by high-density pellet culture. Western blotting and real-time polymerase chain reaction were used to investigate changes in protein and mRNA levels, respectively, during chondrogenesis. Safranin-O staining, immunohistochemistry, and glycoaminoglycan contents were used to assess cartilage matrix deposition. BMSC proliferation was determined by mitochondrial dehydrogenase activity and cell counting. Cell cycle profiling was performed by flow cytometry. Results: LRF overexpression effectively inhibited protein and mRNA expression of chondrocyte markers and cartilage matrix deposition during chondrogenesis of BMSC. Endogenous LRF expression was constitutively high in undifferentiated BMSC but remained low in primary articular chondrocytes. Endogenous LRF protein was downregulated in a time-dependent manner during chondrogenesis. BMSCs overexpressing LRF had higher proliferation rates and cell population in the S phase. LRF suppressed p53 expression during chondrogenesis and this might prevent differentiating chondrocytes from entering a quiescent state. Conclusion: Our data showed that LRF is important for stimulating stem cell proliferation and cell cycle progression. It is known that LRF is highly expressed in the mouse limb buds prior to overt chondrogenesis; thus, LRF might function to prevent premature chondrogenic differentiation of stem cells.